REAKSI PASAR MODAL TERHADAP PERISTIWA VAKSINASI COVID-19 PERTAMA DI INDONESIA - Wijaya, Fenny; Dana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023DO - 10.24843/EEB.2023.v12.i10.p16, 2023)
The first COVID-19 vaccination event in Indonesia which was held on January 13, 2021 is one of an event that occurred in non-economic environment. Thelpurposeioflthis study is to examine whether there were differenceslinlabnormal returns before and after the event. This study uses the event study method on issuers that are incorporated into the LQ45 Index on the Indonesia Stock Exchange using purposive sampling technique and observed for 7 days. Expected return is estimated using the market adjusted model. Hypothesis testing was carried out using the Wilcoxon signed rank test. The results of this study prove that there is no difference in abnormal returns before and after the event. This means that there is no information content in-the-first-COVID-19 vaccination event in Indonesiaxthat could affect the market, so investors in the capital market didn’t react to the event